Sarawak Foundation (Yayasan Sarawak) / Noorbaizura Ismail - Ismail, Noorbaizura (University Technology MARA Sarawak, 2013)
Sarawak independence era in 1963 to record the start of a new challenge for the leaders and people of Sarawak with the development of the standard of education is low; the challenge of providing education for the children of Sarawak is one task that pretty much to bear. With this in mind, the Sarawak Foundation was established in May 27, 1971 by the State Government under the leadership of the Honourable Datuk Haji Abdul Rahman Jacob Patinggi Chief Minister at the time. Armed with a vision that the people of Sarawak should not be behind in terms of education, he has taken the initiative to set up Yayasan Sarawak. He has become the first chairman of the Sarawak Foundation and the Honorable Datuk Amar Abang Haji Yusuf Puteh was appointed as the first Director of Yayasan Sarawak. The establishment of the Sarawak Foundation is dedicated to developing and providing educational facilities and education, to promote unity and loyalty of the people of Sarawak and provide assistance to the families of the armed forces and the police need. Sarawak Foundation is governed by a Board of Trustees headed by a Chairman appointed by the Governor and 4 other members appointed by the Chief Minister. In the first year of its inception, the Foundation has approved a total of 360 Sarawak Scholarship for the purpose. Since then, the Foundation has helped Sarawak students Sarawak and Malaysia in general education.